2018
DOI: 10.1115/1.4040424
|View full text |Cite
|
Sign up to set email alerts
|

Design for Manufacturability-Based Feedback to Mitigate Design Fixation

Abstract: This study assessed the effectiveness of three-dimensional (3D) visual feedback from design for manufacturability (DFM) software on mitigating design fixation on nonproducible manufacturability features. A fixation group and a defixation group were asked to design a basic product for additive manufacturing (AM) and then to modify the next iteration for conventional machining. The fixation group relied on their self-assessment while modifying, while the defixation group utilized dfm software feedback. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our second research question was: Can designers showing evidence of fixation (from either source-a provided example or their own initial example) break away from it in the same session through the use of a design ideation tool? While several idea generation tools have been shown to reduce fixation [23], design heuristics were selected for this study as an example of a design ideation tool supporting idea generation [64]. Design heuristics are empirically tested and shown to be helpful in idea generation [64,69,70,72].…”
Section: Hypothesis 1: Providing Examples Leads To More Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our second research question was: Can designers showing evidence of fixation (from either source-a provided example or their own initial example) break away from it in the same session through the use of a design ideation tool? While several idea generation tools have been shown to reduce fixation [23], design heuristics were selected for this study as an example of a design ideation tool supporting idea generation [64]. Design heuristics are empirically tested and shown to be helpful in idea generation [64,69,70,72].…”
Section: Hypothesis 1: Providing Examples Leads To More Fixationmentioning
confidence: 99%
“…Reviews of this burgeoning research area have explored how variations in cognitive processes lead to fixation, and called for further research to identify how fixation on examples limits the generation of alternatives [10,11,21,22]. Other studies have examined fixation in more varied design settings, including additive manufacturing [23], information system design [24], and "in the wild" [25].…”
Section: Introductionmentioning
confidence: 99%
“…First, studies show signs of design fixation when additive manufacturing is a part of the process (such as prototyping), but conventional methods are ultimately used for larger production (Abdelall et al 2018b). This series of work promotes software to mitigate fixation when moving between the two methods (Abdelall et al 2018a). Designers have also shown a tendency to fixate on manufacturing constraints that have limited past designs when learning new manufacturing capabilities, a concept coined Manufacturing Fixation in Design (MFD) (Bracken Brennan et al 2021).…”
Section: Design Knowledge and Strategiesmentioning
confidence: 99%
“…It has been shown that novice designers in particular can create design fixation, when first designing for AM and then redesigning for traditional manufacturing methods (ibid.). Another study, however, did show that manufacturability software in the concept design phase could assist designers to avoid such design fixation (Abdelall et al, 2018a). In addition to this, the concept of a feature graph has been designed to assist both novice and experienced designers in creating manufacturable designs (Ranjan et al, 2017).…”
Section: Creative Thinking Skills In Relation To Additive Manufacturingmentioning
confidence: 99%